Residual risks of ischaemic stroke and systemic embolism among atrial fibrillation patients with anticoagulation: large-scale real-world data (F-CREATE project). Issue 3 (14th August 2020) - Maeda, Toshiki; Nishi, Takumi; Funakoshi, Shunsuke; Tada, Kazuhiro; Tsuji, Masayoshi; Satoh, Atsushi; Kawazoe, Miki; Yoshimura, Chikara; Arima, Hisatomi
Abstract : Objective: Among patients with atrial fibrillation, the risks of ischaemic stroke and systemic embolism (IS/SE) are high even with effective anticoagulation. Using large-scale, real-world data from Japan, this study aims to clarify residual risks of IS/SE attributable to modifiable risk factors among patients with atrial fibrillation who are taking oral anticoagulants. Methods: The study design we employed was a retrospective cohort. Health check-ups and insurance claims data of Japanese health insurance companies were accumulated from January 2005 to June 2017. We identified 11 848 participants with atrial fibrillation who were on oral anticoagulants during the study period. We set the modifiable risk factors as hypertension, diabetes and dyslipidaemia. A Cox proportional hazards model was used to obtain the effects of the risk factors for IS/SE. Results: During an average of 3 years' follow-up, 200 cases of IS/SE occurred (incidence rate 0.57 per 100 person-years). In multivariable analyses, older age (65–74 vs <65 years; adjusted HR 2.02 (95% CI 1.49 to 2.73)), hypertension (adjusted HR 1.41 (1.04 to 1.92)) and dyslipidaemia (adjusted HR 1.46 (1.07 to 1.98)) were significantly associated with increased risk of IS/SE. Percentage of IS/SE risk attributable to modifiable risk factors (hypertension, diabetes and dyslipidaemia) was 30.0% (16.1% to 41.6%). Conclusion: Among patients with atrial fibrillation on anticoagulant therapy, approximately one-third of the residual risks were estimated to be attributable to modifiable risk factors such as hypertension, diabetes and dyslipidaemia.